2016
DOI: 10.1016/j.apcatb.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic performance of BiPO4 nanorods adjusted via defects

Abstract: The effect of defect on the photocatalytic and photoelectric performance of BiPO4 has been revealed. The bulk defects of BiPO4 such as bismuth vacancies(VBi), oxygen vacancies(VO) and so on were formed during the ball-milling process. These bulk defects of BiPO4 inhibited the separation of photo-generated charges greatly and thus reduced photocatalytic activity. Most of the bulk defects were repaired and the photocatalytic activity of BiPO4 was also recovered mostly via calcination and reflux. Reflux could rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 39 publications
2
77
0
Order By: Relevance
“…During the ball‐milling treatment of graphite, the particle size of ball‐milled graphite will suffer from decrease and more edges/defects are exposed, which is beneficial to the catalytic activity optimizing . With respect to the ball‐milling treated BiPO 4 , Zhu et al found that numerous defects of BiPO 4 such as Bi vacancies, O vacancies were formed during the ball‐milling process . However, since the formed defects were bulk defects, which inhibited the separation of photogenerated charges, thus reduced the photocatalytic activity.…”
Section: Strategies For Controlling Defects Formationmentioning
confidence: 99%
“…During the ball‐milling treatment of graphite, the particle size of ball‐milled graphite will suffer from decrease and more edges/defects are exposed, which is beneficial to the catalytic activity optimizing . With respect to the ball‐milling treated BiPO 4 , Zhu et al found that numerous defects of BiPO 4 such as Bi vacancies, O vacancies were formed during the ball‐milling process . However, since the formed defects were bulk defects, which inhibited the separation of photogenerated charges, thus reduced the photocatalytic activity.…”
Section: Strategies For Controlling Defects Formationmentioning
confidence: 99%
“…Bismuth phosphate BiPO 4 has been studied as a photocatalytic material, as it shows good photocatalytic performance . However, there have been few reports about BiPO 4 being used as electrode materials in supercapacitors.…”
Section: Metal Phosphidesmentioning
confidence: 99%
“…[41] As g-C3N4 transforms from nano-plates to nano-rods, the improvements of photo-catalysis and photocurrent intensity in g-C3N4 nano-rods probably resulted from the increase of active lattice face and decrease of surface defects. [41,140] Substrate-assisted hydrothermal method is also an interesting idea to fabricate g-C3N4 nano-ribbons. Zhao et al reported a 3D assembly architecture of 1D g-C3N4 nano-ribbons with 2D graphene sheets via a one-step hydrothermal method.…”
Section: Nanorod Structurementioning
confidence: 99%